Analisa Perancangan Ulang (Redesain) Model Operasionalisasi Program Bantuan Operasional Sekolah Dalam Meningkatkan Efektivitas Penyelenggaraan Pendidikan dan Memenuhi Harapan Masyarakat - Hesti Maheswari; Luna Haningsih (Jurnal Manajemen dan Bisnis Indonesia, 2014)
This study aims to establish a model operationalization BOS program, through the analysis of Quality Function Deployment. This study was based on the presence of a variety of complaints that come from the communities to the BOS program that they can not benefit from the one hand, and the other side the Government felt that the implementation of BOS has reached three rights are the right time, the right amount, and on target. Public dissatisfaction conditions to the program evidenced by the high dropout rates.The extent to which the BOS program helps students in education funding, in turn raises a big question mark because of government policies and rhetoric seem apparent.Because it was the children of farmers, laborers, street vendors, low class servants, janitors still do not get the ease and lightness in education.Free school which echoed the Government would make society under increasingly sad to hear that. The first results of this study is the expectationof the people to the BOS program, namely:most of BOS funds can be used to offset the cost of student transportation, schools have adequate science laboratories and maximum usage, quality textbooks provided by the school, BOS program can ease the burden of school, students can discuss with the teacher outside of school hours, andSchool Committee oversees use of the funds. From this analysis known gap formed between community expectations with the level of BOS concept is still very high, both western and central regions Indonesia.Researchers feel that there is no proper policy of the Government to secure the nation's ideals in improving quality through Learning Program 9 years.Therefore, we need strategies to be more comprehensive to narrow the gap between idealism with the realities on the ground, so that education becomes more obvious problems 'roots' and more 'effective and efficient' ways to overcome. Redesigns recommended are monitoring and evaluation, increase teacher motivation, integrated management system, operational guidelines for use of the funds, supervision attached, and additional facilities. To accomplish these results it is necessary to continue the research terms, that is for two eastern Indonesia: Maluku and Papua. Keywords: recommendation of operationalization model BOS program, quality function deployment